Persepsi Mahasiswa Geografi Universitas Siliwangi Tentang Kertas Daur Ulang Sebagai Edukasi Lingkungan dan Ekonomi Kreatif - Berinda Cesilla Azwar; Rizka Annisa Nur’alim; Muhamad Rifki Saputra (Universitas Negeri Gorontalo, 2025)
Rising paper consumption in the education sector contributes to deforestation and waste, challenging the balance between education and environmental sustainability. This study investigates the perceptions of Geography Education students at Universitas Siliwangi regarding paper recycling as a tool for environmental education and creative economy opportunities. Using a quantitative approach, 50 students from the 2020, 2023, and 2024 cohorts completed a 4-point Likert-scale questionnaire. Findings reveal that most students agree that paper recycling promotes the 5R principles in environmental education and recognizes its economic potential through the creation of value-added products. Nonetheless, students also note the risk of generating additional waste if recycling is not managed properly. The study concludes that paper recycling can effectively reduce waste when implemented thoughtfully and sustainably.